2019
DOI: 10.1093/neuonc/noz216
|View full text |Cite|
|
Sign up to set email alerts
|

Extensive brainstem infiltration, not mass effect, is a common feature of end-stage cerebral glioblastomas

Abstract: Background Progress in extending the survival of glioblastoma (GBM) patients has been slow. A better understanding of why patient survival remains poor is critical to developing new strategies. Postmortem studies on GBM can shed light on why patients are dying. Methods The brains of 33 GBM patients were autopsied and examined for gross and microscopic abnormalities. Clinical-pathologic correlations were accomplished through d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Treating the resection cavity with the virus or intravenous virus administration after surgery can reduce the risk of relapse by inhibiting the growth of GSCs. It is known that a population of GSCs is capable of self-renewal, proliferation, and invasion, and can cause local recurrence around the surgical site and/or non-local recurrence in the remainder [31,32]. Possible combinatorial therapy is used to reduce the risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Treating the resection cavity with the virus or intravenous virus administration after surgery can reduce the risk of relapse by inhibiting the growth of GSCs. It is known that a population of GSCs is capable of self-renewal, proliferation, and invasion, and can cause local recurrence around the surgical site and/or non-local recurrence in the remainder [31,32]. Possible combinatorial therapy is used to reduce the risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the extensive infiltration of tumors into the brainstem is consistent with our previous study of end-stage gliomas, particularly those with a protracted disease course. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The role of cadherins in glioma progression is not well-understood yet. However, the interaction between CSCs and other cellular components of the TME, such as those forming the white matter tracts that glioma cells used to migrate through or ECs from the BBB, has recently acquired great relevance (Drumm et al, 2019 ). Although previous studies reported differing results regarding the concentration level of cadherins and glioma cell invasion capacity, it was finally clear that rather than the concentration of cadherins available, the most important factor determining migration and invasiveness in GBM cell lines was the instability and disorganization of cadherin-mediated junctions (Barami et al, 2006 ).…”
Section: Role Of Tumor Microenvironment In Glioma Biologymentioning
confidence: 99%